1994
DOI: 10.1007/bf00203488
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary generalized juvenile polyposis: Association with arteriovenous malformations and risk of malignancy

Abstract: A young man with hereditary juvenile polyposis, a duodenal adenoma with carcinoma in situ, and multiple arteriovenous malformations of the lungs and liver is reported. Because of the risk of malignancy, it is suggested that patients with juvenile polyposis have endoscopic or radiographic surveillance of the upper gastrointestinal tract in addition to either prophylactic colectomy or regular colonoscopic surveillance with polypectomy. In view of the serious potential complications of associated pulmonary, cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…In the aggregate, this SMAD4 mutation‐positive JP–HHT cohort displayed the full range of clinical features associated with HHT as defined by the Curaçao criteria [Shovlin et al, 2000]. Thirteen patients exhibited PAVMs, consistent with previous reports of JP patients with PAVMs [Cox et al, 1980; Conte et al, 1982; Baert et al, 1983; Prieto et al, 1990; Radin, 1994; Schumacher et al, 1994; Desai et al, 1998; Inoue et al, 1999; Burger et al, 2002]. One patient with a PAVM also had a liver AVM, and one patient with a PAVM also had a cerebral AVM.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…In the aggregate, this SMAD4 mutation‐positive JP–HHT cohort displayed the full range of clinical features associated with HHT as defined by the Curaçao criteria [Shovlin et al, 2000]. Thirteen patients exhibited PAVMs, consistent with previous reports of JP patients with PAVMs [Cox et al, 1980; Conte et al, 1982; Baert et al, 1983; Prieto et al, 1990; Radin, 1994; Schumacher et al, 1994; Desai et al, 1998; Inoue et al, 1999; Burger et al, 2002]. One patient with a PAVM also had a liver AVM, and one patient with a PAVM also had a cerebral AVM.…”
Section: Resultssupporting
confidence: 82%
“…Although there had been reports in the medical literature of JP patients with associated HHT or HHT‐like symptoms, most notably pulmonary AVMs (PAVMs), these observations did not originally point to any specific genetic cause [Cox et al, 1980; Conte et al, 1982; Baert et al, 1983; Prieto et al, 1990; Radin, 1994; Schumacher et al, 1994; Desai et al, 1998; Ballauff and Koletzko, 1999; Inoue et al, 1999]. A combined syndrome, JP–HHT, is now recognized [Gallione et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that JP patients sometimes exhibit various extraintestinal manifestations. Among such manifestations, pulmonary arteriovenous malformations are the most frequently described [Cox et al, 1980; Baert et al, 1983; Prieto et al, 1990; Radin, 1994; Schumacher et al, 1994; Inoue et al, 1999; Gillespie and McIvor, 2001]. Recently, a combined syndrome of JP and HHT was suggested [Gallione et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…Hereditary hemorrhagic teleangiectasia (Osler-Weber-Rendu syndrome) is an autosomal dominant Although considerable variation in reports exists, it seems evident that JP patients carry an increased risk of colorectal and possibly gastric cancer. Case reports of juvenile polyposis patients with symptoms of HHT, including arteriovenous malformations in the lung [80][81][82][83], liver [82,83], and skin [83] and gastrointestinal teleangiectasias [81,82], raised the suggestion of a common genetic cause for these two syndromes. (4).…”
Section: Extra-intestinal Manifestationsmentioning
confidence: 99%
“…In JP patients with germline SMAD4 or ENG mutations, screening should be considered for arteriovenous malformations using chest radiography, magnetic resonance imaging of the brain and liver sonography [82,84]. In addition, digital clubbing and pulmonary osteoarthropathy are frequently described in combination with arteriovenous malformations [78,80].…”
Section: Genetic Defectmentioning
confidence: 99%